2006
DOI: 10.1172/jci27597
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human PAC1 receptor leads to dose-dependent hydrocephalus-related abnormalities in mice

Abstract: Hydrocephalus is a common and potentially devastating birth defect affecting the CNS, and its relationship with G protein-coupled receptors (GPCRs) is unknown. We have expressed 2, 4, or 6 copies of a GPCR--the human PAC1 receptor with a 130-kb transgene in the mouse nervous system in a pattern closely resembling that of the endogenous gene. Consistent with PAC1 actions, PKA and PKC activity were elevated in the brains of Tg mice. Remarkably, Tg mice developed dose-dependent hydrocephalus-like characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…Primary neuronal culture was conducted as described previously (Lang et al, 2006). Briefly, 24-well plates were precoated with poly-L-ornithine (Sigma) for 1 h followed with fibronectin (Invitrogen) for 2 h. The newborns were genotyped by PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary neuronal culture was conducted as described previously (Lang et al, 2006). Briefly, 24-well plates were precoated with poly-L-ornithine (Sigma) for 1 h followed with fibronectin (Invitrogen) for 2 h. The newborns were genotyped by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Sections were processed immunohistochemically as described previously (Lang et al, 2006). The primary antibodies included mouse anti-BrdU (1:200; BD Biosciences) and rabbit anti-parvalbumin (1:1500; Swant).…”
Section: Methodsmentioning
confidence: 99%
“…The present study has confirmed the involvement of cAMP in the control of ciliary function, as ACT was shown to significantly decrease ciliary amplitude. In line with these findings, mice overexpressing PAC1 receptor have been shown to have elevated PKA and PKC activity, ciliary defects and increased apoptosis, resulting in development of hydrocephalus (Lang et al, 2006).…”
Section: Discussionmentioning
confidence: 61%
“…Namely, PAC1 overexpressing mice showed a higher level of PAC1 expression especially in ventricle-surrounding regions, when compared to wild type (Lang et al, 2006). In the developing brain, PAC1 mRNA expression showed more intense subventricular localization (Basille et al, 2000;Jaworski and Proctor, 2000;Zhou et al, 1999) than in the adult (Hashimoto et al, 1996;Jaworski and Proctor, 2000;Shioda et al, 1997).…”
Section: Studies Onmentioning
confidence: 89%
See 1 more Smart Citation